Band engineering at the interface of all-inorganic CsPbI2Br solar cells. Issue 31 (25th July 2019) - Zhuang, Jing; Wei, Yuanzhi; Luan, Yigang; Chen, Ningli; Mao, Peng; Cao, Shaokui; Wang, Jizheng
Abstract : An all-inorganic CsPbI2 Br perovskite with excellent phase stability and thermal stability has been considered to be a promising candidate for photovoltaic application. Abstract : An all-inorganic CsPbI2 Br perovskite with excellent phase stability and thermal stability has been considered to be a promising candidate for photovoltaic application. However, low efficiency and high moisture sensitivity hinder its advancement. In this work, we exploit 4-bromobenzylamine hydriodate post-treatment on CsPbI2 Br thin films to assist the extraction of holes and to block the flow of electrons to the hole transport layer through band engineering at the CsPbI2 Br bulk/surface. We found through depth profile analysis that a small amount of BrBeAI permeates into the CsPbI2 Br bulk and mainly locates at the CsPbI2 Br grain boundaries. This treatment leads to an improved short-circuit current of CsPbI2 Br solar cells and an enhanced efficiency from 13.10% to 14.63%. In addition, the incorporation of the hydrophobic organic component into perovskite films effectively enhances the moisture resistance. This result proves that utilizing organic ammonium salt to improve the performance of the device through band alignment is an effective strategy for all-inorganic perovskite solar cell optimization.